Asia's sectoral transformation, evolving diets, and the consequences for climate change - Donald F. Larson (Asian Development Bank Institute (ADBI), 2024)
Established by the United Nations in 2015 with a target date of 2030, the Sustainable Development Goals (SDGs) provide a framework with specific objectives to guide global development policy. The SDGs extend and modify an earlier framework, the Millennium Development Goals (MDGs), established in 2000 with a target date of 2015. Goal 1 of the MDGs was to eradicate extreme poverty and hunger, with the specific goals of halving the proportions of both undernourished and malnourished people between 1990 and 2015. The poverty goal was met fully, ahead of schedule, and substantive progress was made toward the hunger goal due, in large part, to gains in agricultural production and productivity. Building on this progress, SDG 2 aims to "end hunger" and "achieve food security and improved nutrition," while promoting "sustainable agriculture." Lifting millions of families from the desperate cycle of hunger and poverty also had consequences for the environment. Roughly 72% of the world's freshwater supplies go to agriculture; in South Asia, agriculture uses over 90%. On-farm greenhouse gas emissions (GHGs) are growing too. Global on-farm GHG emissions grew by about 10% between 1990 and 2020, from 6.7 to 7.4 GtCO2e; in Asia, during the same period, on-farm GHG emissions grew by 27%, from 2.5 to 3.2 GtCO2e. All of this puts agriculture and food systems at odds with other SDG goals, particularly Goal 6, which calls for efforts to better manage water supplies; Goal 12, which aims to reduce agriculture's environmental footprint; and Goal 13, which calls for urgent action to combat climate change. This paper looks at how past technology choices opened a pathway to prosperity in Asia that now threatens the region's natural resources and the stability of the planet's climate. Specifically, the paper focuses on the greenhouse gas emissions from two practices, the cultivation of paddy rice and the growth in livestock production, in 15 countries in South and Southeast Asia, which collectively account for more than 80% of the global emissions from each practice. Based on country-specific habit-formation models of dietary choice estimated from a 15-country panel of annual data from 1970 to 2020, out-of-sample projections show that business-as-usual emissions from rice production and animal waste will increase by 57% and 204%, respectively, over the next three decades. The projections are robust to alternative assumptions about income growth. This illustrates how the past success of the intensive agricultural technologies, and the income gains they helped spur, has led to still-ongoing dietary transitions that will complicate and hinder future efforts to reduce on-farm emissions, as researchers and policymakers strive to foster greener technologies to reduce agriculture's environmental footprint - technologies that must also sustain continued productivity gains if all SDGs are to be met.
Keywords: C33; Q16; Q31; Q32; Q38; Q54; 330; agriculture; Asia; diets; economic development; frontier estimator; greenhouse gas emissions; livestock; poverty; rice; Sustainable Development Goals; technology